Proteolysis, microbiology, volatiles and sensory evaluation of Algerian traditional cheese Bouhezza made using goat's raw milk. (31st December 2017) - Medjoudj, Hacène; Aouar, Lamia; Zidoune, Mohammed Nasreddine; Hayaloglu, Ali Adnan
ABSTRACT: The objective of this work was to characterize the traditional cheese, Bouhezza made with raw goat's milk. There were three cheese making performed; two at the laboratory scale (FH1, FH2) and one in a farm (FH3). The evaluation consisted in the determination of physico-chemical characteristics, proteolysis, microbiological and sensory status. The microbiological characterization was performed during cheese ripening with identification of lactic acid bacteria by 16S rDNA sequencing using PCR-TTGE. The sensory analysis and volatile profile were determined by GC-MS. The pH decreased during cheese ripening from 4.69 to 3.99. The moisture in defatted cheese was 79.05% and fat-in-dry matter 34.77%, which allowed its classification according to the Codex alimentarius as ripened soft and mid-fat cheese. The urea-PAGE pattern of caseins showed a fast proteolysis, which started from the first day of ripening. The sensory evaluation showed that Bouhezza cheese was salty, spicy and intense in odour and aroma. A total, of 100 volatile compounds were identified, where the main components were carboxylic acids (14 compounds) followed by their esters (32) and alcohols (13), aldehydes (5), ketones (8), terpenes and miscellaneous compounds. This study showed that Bouhezza cheese was considered as a product of satisfactory microbiological quality and rich in LABs whose contribute to its ripening, where many of identified strains were the same as those found in other dairy products. The main sensory descriptors as flavour and odor, was lactic flavor and lactic acidic odor. The products of proteolysis gives to Bouhezza a riches in volatiles and fragrance characteristics, which reflect the uniqueness of this cheese of terroir. Finally, an identity card of the Bouhezza cheese was achieved following results of this study.